Adherence of Aeromonas hydrophila strains to human enterocyte-like cells pre-infected with rotavirus - Bertuccio, M P; Picerno, I; Scoglio, M E (Journal of preventive medicine and hygiene, 2012)
The interest grown in these years about emerging pathogens in the onset of intestinal disease showed that the pathogenic mechanism is a multifactorial event. Our objective was to evaluate the role of co-infection with rotavirus in the expression of Aeromonas spp adhesiveness. The rate of co-infection involves contact of Caco-2 cells with the virus, followed by adsorption for 1 and 2 hours. Aliquots of bacterial suspensions were added to tissue-culture plates. After infection, cell monolayers were lysed; serially diluted lysates were plated to determine the number of bound bacteria by performing colony forming units (CFU) counts. Non-adhesive strains were not subject to variations resulting from co-infection, while those who had medium or high adhesiveness gave rise to an increase of the same. Infection with rotavirus promotes the Aeromonas ability to adhere to Caco-2 cells and this effect depends on the duration of infection and on the starting adhesiveness of bacteria strain.